Improving Science Learning Outcomes in Fourth Grade Students through Guided Inquiry Learning with Audio-Visual Media - Widiawati, Ni Kadek Mega; Rati, Ni Wayan; Yudiana, Kadek (Universitas Pendidikan Ganesha, 2020)
Low science learning outcomes are one of the problems in this study. This study aimed to analyze the effect of a guided inquiry learning model assisted by audio-visual media on fourth-grade elementary school students' science learning outcomes. This type of research is a quasi-experimental research design with a post-test only control group design. This study's population amounted to 182 students, while the sampling in this study used a random sampling technique. In this study, the data collection method used the test method, and the research instrument used the selected objective test. Methods and data analysis techniques through descriptive statistical tests, prerequisite tests, and t-test. This study's results indicate that the results of the t-test with a 5% significant level and with dk = 42 obtained tcount> ttable (4.212> 2.018), which means that H0 is rejected while H1 is accepted. This study concludes that the guided inquiry learning model assisted by audio-visual media affects fourth-grade elementary school students' science learning outcomes. This research implies that this research can allow teachers to develop teaching skills using innovative learning models and learning media and affect student learning outcomes.